Cold spray synthesized hydroxyapatite-magnesium bioimplants physico-chemical behaviour, adherence and environmental compatibility - Hussain, Zuhailawati (Universiti Sains Malaysia, 2014)
'^^^^'^'^mple and modified cold spray processwas developed In which hydroxyapatlte powderwas coated onto pure magnesium substrates preheated to 350°C or 550-C and ground to either 240 gnt or 2000 grit surface roughness, with standoff distances of 20 mm or 40 mm. The procedure was repeated five and ten times Afractional factorial design (2^') was applied to elucidate the process factors that significantly affected the thickness, nanohardness and elastic modulus of the coating sample. The overlaid method analysis was employed to determine trade off optimal values from multiple responses which is thickness, nanohardness and elastic modulus of the coating. Then, steepest method was used to reconfirm and relocate tee op ^ domain. The maximum mechanical properties of tee coating were determined at 30mm standoff distance, 926 4grit surface roughness and 456'C substrate heating temperature which accommodate t eop imum coating of 49.77pm thickness, 462.61 MPa nanohardness and 45.69 GPa elastic modulus. e hydroxyapatlte coatings did not show any phase changes at 550"C. Atomic force mlaoscopy revealed a uniform coating topography and scanning electron microscopy revealed good bonding ^ layers and tee substrates. The biodegradable study suggested that the bone-like apatite layer formed tee surface of the coatings at 1140 minutes may promote the bone bonding with living tissues and mcmase the ] longevity of coatings. The mass loss experiment concluded teat coated sample shows abetter bioachvity compare to uncoated sample. The adhesion test revealed teat reduction of bond strength comes mostly from tee continuation of chemical dissolution of coatings. At 1140 minutes of Immersion, tee bond ^t^^ng hwas 40 Mpa which satisfied the requirement for blolmplant application. The accelerated corrosion test concluded teat tee HAP coating remarkably protect and prevent from tee corrosion In tee corrosive environment. RU Grant